Systematics of Andean Lupinus L. and the origin of L. mutabilis Sweet - Eastwood, RJ (2006)
This thesis contributes to the central goals of systematics - the inventory of species, building the tree of life and understanding evolutionary processes - through a descriptive taxonomic study, molecular phylogenetic analysis and morphological survey of the genus Lupinus L.